Examining the Implementation and Execution of Lean Thinking and Tools in Construction Sector in Developing Courities - MUTAWEODEH, MASA (İstanbul Kültür Üniversitesi, 2023)
Palestine faces many issues within the construction sector, including cost, time overrun, performance quality, and management. To deal with these issues, the industry must adopt lean management principles as the new approach to solving such problems. The study aims to investigate the obstacles that impact the execution of lean thinking and tools in Palestine as a developing country and its impact on waste related to construction sites through a questioner which filled out by the target sample of construction companies, engineers, construction workers and expertise in Ramallah the industrial capital and Nablus. The collected sample was 91 responses. These responses are applied in SPSS software to find results through 1- principle component analysis, 2- reliability analysis, 3- multiple regression and correlation analysis, and 4- measure for association and correlation. The result shows that Planning and management issues significantly affect the execution of lean management approaches successfully. With the formula of CC= +0.167 *C1. Where C1 is the planning and management component, and CC is the core concept. This study recommends that the construction companies and the education system regarding these university curriculums must keep continuous improvement related to the knowledge regarding lean construction management approaches, and apply LCM in their projects, to overcome the management issues. Keywords:
Gelişmekte Olan Ülkelerde İnşaat Sektöründe Yalin Düşünceve Araçlarinin Uygulanmasi ve Yürütülmesinin İncelenmesi
▪ Yüksek lisans tezi.
Keywords: Lean Construction Management; Construction Projects; Just in Time; Visual Management; Planning; Management